2022
DOI: 10.3390/antibiotics11030290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotic Prophylaxis on Surgical Site Infection in Thyroid and Parathyroid Surgery: A Systematic Review and Meta-Analysis

Abstract: Thyroid and parathyroid surgery are considered clean procedures, with an incidence of surgical site infection (SSI) after thyroidectomy ranging from 0.09% to 2.9%. International guidelines do not recommend routine antibiotic prophylaxis (AP), while AP seems to be employed commonly in clinical practice. The purpose of this systematic review is analyzing whether the postoperative SSI rate in thyroid and parathyroid surgery is altered by the practice of AP. We searched Pubmed, Scopus, the Cochrane Library, and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Myssiorek et al reported that age ≥80 years, male sex, BMI of 40–50 kg/m 2 , current smoking and ventilation within 48 hours preceding surgery are also risk factors 23 . Generally, thyroid surgery is a clean procedure, and prophylactic antibiotics are not recommended 24‐27 . However, we argue that prophylactic antibiotics should also be considered in thyroid surgery, as the incidence of SSI is three to four times higher in patients with a general condition worse than ASA 3 and in those whose operation lasts longer than the duration of surgery in the 75th percentile or above.…”
Section: Discussionmentioning
confidence: 83%
“…Myssiorek et al reported that age ≥80 years, male sex, BMI of 40–50 kg/m 2 , current smoking and ventilation within 48 hours preceding surgery are also risk factors 23 . Generally, thyroid surgery is a clean procedure, and prophylactic antibiotics are not recommended 24‐27 . However, we argue that prophylactic antibiotics should also be considered in thyroid surgery, as the incidence of SSI is three to four times higher in patients with a general condition worse than ASA 3 and in those whose operation lasts longer than the duration of surgery in the 75th percentile or above.…”
Section: Discussionmentioning
confidence: 83%
“…Morbidity is mainly represented by hypoparathyroidism, recurrent laryngeal nerve injury, cervical haematoma and wound infection. These complications lead to a reduction in the quality of life of the patients and increased costs for healthcare systems [24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…It results in no skin scarring and requires only a relatively small skin flap in the gingival mucosa. In conventional open thyroidectomy, there is no need for prophylactic antibiotics usage to prevent surgical site infection because the thyroidectomy wound that occurs as a result of the use of an anterior neck approach is a clean wound ( 9 ). However, in TOET surgery, the oral cavity is the incision site and this is considered part of the alimentary tract, so the TOET wound is not considered a clean wound, but a clean-contaminated wound ( 4 , 10 ).…”
Section: Discussionmentioning
confidence: 99%